2017
DOI: 10.1521/soco.2017.35.5.497
|View full text |Cite
|
Sign up to set email alerts
|

Social Perception in the Volunteer's Dilemma: Role of Choice, Outcome, and Expectation

Abstract: The volunteer's dilemma (VoD) is a challenging interpersonal situation in which one person must bear a cost for the benefit of the group. If no one volunteers, all suffer. Research shows that many individuals are willing to volunteer, but little is known about the impressions volunteers and defectors make on social perceivers. In three studies, we find that observers judge volunteers to be more competent and more moral than defectors. The outcome of the dilemma, as co-determined by the other person's decision,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(67 reference statements)
1
8
0
Order By: Relevance
“…However, they are of limited use in the case of unilateral interactions -which are the focus of the current study -where beliefs about the intentions of others do not apply. Reputation-based models (e.g., Heck & Krueger, 2017;Jordan et al, 2016;Nowak & Sigmund, 2005) also appear of limited use for our results because choices were anonymous and one-shot.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are of limited use in the case of unilateral interactions -which are the focus of the current study -where beliefs about the intentions of others do not apply. Reputation-based models (e.g., Heck & Krueger, 2017;Jordan et al, 2016;Nowak & Sigmund, 2005) also appear of limited use for our results because choices were anonymous and one-shot.…”
Section: Discussionmentioning
confidence: 99%
“…Third, participants’ own willingness to volunteer was higher than their expectations that other individuals would. This pattern indicates self-enhancement because volunteering is valued highly in moral terms (Heck & Krueger, 2017).…”
Section: Psychological Heuristicsmentioning
confidence: 99%
“…People care about their good name, and acts of volunteering maintain it; acts of defection do not. In a series of vignette studies, we found that observers rewarded volunteers with ascriptions of warmth and trustworthiness no matter what the other player did (Heck & Krueger, 2017). They even described mutual volunteers as more competent than unilateral volunteers.…”
Section: Egocentric Myopiamentioning
confidence: 99%
“…As reviewed in Krueger et al (2020), previous studies have examined how people evaluate a target's morality and competence in various situations of social dilemmas. One of the studies investigated the way people perceived a target's morality and competence in a situation of the VoD (Heck & Krueger, 2017). These authors conducted scenario-based experiments and found that the target was more likely to be seen as moral and competent when they volunteered than when they did not.…”
Section: Prosocial Behaviour and Social Rewardsmentioning
confidence: 99%
“…When Heck and Krueger (2017) revealed how people obtain social rewards in the VoD, they used scenarios that depicted a situation where the target in a group of two facing the VoD chose whether to volunteer or not to volunteer based on a payoff matrix, without any knowledge of the other group member's decision. Such a situation is very different from the VoD in everyday life, where people make a volunteering or shirking decision based on the subjective costs and benefits, with information about other members' attitudes.…”
Section: Prosocial Behaviour and Social Rewardsmentioning
confidence: 99%